2013
DOI: 10.1186/1029-242x-2013-105
|View full text |Cite
|
Sign up to set email alerts
|

On the convergence of a kind of q-gamma operators

Abstract: In this paper, we introduce a kind of q-gamma operators based on the concept of a q-integral. We estimate moments of these operators and establish direct and local approximation theorems of the operators. The estimates on the rate of convergence and weighted approximation of the operators are obtained, a Voronovskaya asymptotic formula is also presented. MSC: 41A10; 41A25; 41A36

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 7 publications
(1 reference statement)
1
16
0
Order By: Relevance
“…Therefore, ROS have been implicated in cutaneous ageing as well as in the pathogenesis of inflammatory skin diseases and skin cancer (8). Phlorizin has been reported to have antidiabetic effects due to its antioxidant properties (6). In our study, we observed that phlorizin can inhibit the overproduction of ROS induced by UVB irradiation in skin keratinocytes.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Therefore, ROS have been implicated in cutaneous ageing as well as in the pathogenesis of inflammatory skin diseases and skin cancer (8). Phlorizin has been reported to have antidiabetic effects due to its antioxidant properties (6). In our study, we observed that phlorizin can inhibit the overproduction of ROS induced by UVB irradiation in skin keratinocytes.…”
Section: Discussionsupporting
confidence: 52%
“…Phlorizin (phloretin-2-O-glucoside), a dihydrochalcone derived from apple bark, is known to produce renal glycosuria and block intestinal glucose absorption through inhibition of sodium/glucose cotransporters in the kidney and intestine (6). Recently, phlorizin and its analogues are being investigated for the treatment of diabetes, obesity and stress hyperglycaemia (7).…”
Section: Introductionmentioning
confidence: 99%
“…Later, many researchers have performed studies in this field, and the q-analogue of classical operators and modified operators, such as q-Szász-Mirakjan operators [28], q-Baskakov operators [13], q-Meyer-König-Zeller operators [12], q-Bleimann-Butzer-Hann operators [11] q-Phillips operators [29], q-Baskakov-Kantorovich operators [20], q-Baskakov-Durrmeyer operators [19], q-Szász-beta operators [18], and q-Meyer-König-Zeller-Durrmeyer operators [15], has been constructed; see also [2]. In [6], Cai and Zeng defined q-gamma operators…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many well-known approximation operators with (p, q)-integer, such as (p, q)-Bernstein-Stancu-Schurer-Kantorovich operators [8], (p, q)-Szász-Baskakov operators [16], (p, q)-Baskakov-beta operators [30] have been introduced. All this achievement motivates us to construct the (p, q)-analogue of the gamma operator (1), as we know that many researchers have studied approximation properties of the gamma operators and their modifications (see [7,9,24,39]). The rest of the paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…in some function spaces. Very recently, Cai and Zeng [2] proposed a kind of modified q-generalization of Gamma operators and studied their approximation properties. The modified q-Gamma operators were defined in [2] as follows:…”
Section: Introductionmentioning
confidence: 99%